PEMUNGUTAN PAJAK HOTEL DI KABUPATEN KUANTAN SISINGI TAHUN 2016 - Oktario Candra; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Charges as one source of State income, to the State. Kuantan Singingi Regency has been a lot of development and dissemination of facilities and infrastructure that support the sector and in regional development in Kuantan Singingi Regency especially in the availability of development facilities. One of the availability of development facilities in Kuantan Singingi Regency is the availability of hotels and guesthouses for Kuantan Singingi district visitors. As the hotel develops and accelerates, it can affect local revenue through hotel and guest charges. In 2016, hotel and guesthouse charges revenues have decreased significantly from the previous year. Thepurpose of this research is to know the Implementation of Regional Regulation of Kuantan Singingi Number 02 Year 2011 About Hotel charges . This research uses descriptive research type because in this research to know the main problem that is Implementation of Regulation of Regency of Kuantan Singingi Number 2 Year 2011 about Hotel charges.The results of this study is the Implementation of Local Regulation No. 02 of 2011 on Hotel Taxes in the District Revenue Office of Kuantan Singingi conducted in accordance with the existing rules on the Regulation No. 02 of 2011 on Hotel charges. For hotel owners who do not pay the hotel charges will be followed in accordance with the rules on the Local Regulation No. 02 of 2011 on Hotel Tax, so Pelasanaan on Local Regulation No. 02 of 2011 on Hotel charges in Kuantan Singingi Regency can be quite well done.Keywords : Implementation, Local Regulation No. 02 Year 2011